Risk Management : So Critical, yet So Elusive - Razook, Chris (World Bank, Washington, DC, 2012)
Every good organization around the globe firmly espouses the benefits of sound risk management. Certainly, the recent financial crisis has underscored this imperative. Yet it is remarkable how elusive an effective risk management function can be for many organizations. This is definitely the case for many of the companies the authors have worked with as part of the corporate governance program in the Middle East and North Africa (MENA) region. This smart lesson is based on the recent work with an investee company to help put in place a simple but effective enterprise risk management process. This was part of a wider corporate governance improvement effort for the company. It also draws on experiences we've had with other companies and provides lessons for any organization trying to figure out how to actually make risk management work.